(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
the research covers the possibility of obtaining high-octane fuel additives based on fractionating heavy hexane, which is a waste product of the gas and chemical industry, and its chemical modification through oxidation, isomerization, alkylation, etherification and interesterification processes. The composition of the fractions extracted in different temperature ranges was analyzed using gas chromatography-mass spectrometry (GC–MS) and infrared spectroscopy (IRS). The results of the research showed that branched hydrocarbons, oxygenated ethers and alcohols are formed as a result of chemical processing and that they significantly increase the octane number of motor fuels. When the obtained additives were mixed with AI-80, the octane number increased to the appropriate point, which indicates an improvement in fuel quality, and in chemically modified samples, the highest result was found to be up to 97. The research findings establish a scientific and practical framework for developing environmentally sustainable and cost-efficient octane-boosting additives derived from the deep processing of hydrocarbon waste.